Upgrading the Admission Code Status Discussion: A Curriculum for Medical Trainees - Lynnea Mills; Caroline Rhoads; Jared Curtis (Association of American Medical Colleges, 2015)
Abstract Introduction Experts on code status discussions have recommended and utilized a particular approach to the code status discussion that involves eliciting patient goals, and recommending a code status if one aligns with those goals. Yet residents who conduct the majority of the code status discussions at academic institutions rarely receive training to help them meet these guidelines and recommendations, and may therefore lack the skills necessary to conduct the code status discussion. This curriculum arose out of a perceived need to offer internal medical residents a standardized curriculum, grounded in existing guidelines and evidence, which would allow them to become more skilled and comfortable with code status discussions. Methods The curriculum aims to take experts' best practices for the code status discussion and make them both available to and appropriate for early trainees. The curriculum consists of two sessions of approximately 1 hour each, both based on PowerPoint presentations formatted to spark extensive discussion amongst learners. The curriculum can be taught by anyone with moderate experience with code status discussions and is designed to minimize the planning required on the part of the instructor. Results We piloted this curriculum with 15 interns during the 2013-2014 academic year. Immediately after participation in the curriculum, the interns were surveyed anonymously about the curriculum and we solicited in-person feedback. One hundred percent of participants could accurately state usual code outcomes after participating in the curriculum, compared to just 40% beforehand. When asked if they'd recommend the curriculum to future interns (1 = definitely not, 5 = definitely), their average response was 4.5. When asked how well the sessions prepared them to engage in further code status discussions with real patients, they rated them as 4.3, on average, and they gave an average rating of 4.6 when asked how effective the curriculum's examples were in giving them ideas for phrasing to use in real patient conversations. They average response to "How comfortable would you feel using this new framework in a code status discussion?" was 4.0. When asked to perform blind recall of the seven steps in the described process, the group overall recalled the steps 81% correctly. Representative narrative comments included: "Wish I'd had this training earlier," and "I really appreciate the perspective. I will try it out today." Discussion Due to the success of this curriculum, it was discussed during a departmental Grand Rounds presentation and was made accessible to outside providers; we received requests from other institutions, who were enthusiastic about the mnemonic utilized in this resource, to present this approach to their own trainees.